Penguatan literasi siswa melalui program pojok buku dan penyusunan modul bahasa di MI Al-Lathifiyah Gedog Wetan, Turen - Husna, Nurul Aliefiatul; Sufi, Ahmad Ibnu; Shifak, Huril Dewi; Setiyaningrum, Riskayani; Shomad, Moch Mawahibus; Lazuardhi, Alex Febryan; Urrochmana, Muhammad Auliya; Ashilah, Tachriza Nur; Mustofa, David Irda Shilahul; Agung, Yusuf Ratu (Maliki Interdisciplinary Journal, 2026)
The school literacy program is one of the important strategies in improving the reading and writing skills of elementary school students. MI Al-Lathifiyah Gedog Wetan, Turen, faces obstacles in the form of limited reading facilities and the unavailability of teaching materials that are interesting for students. This community service activity aims to strengthen the culture of literacy through the creation of book corners in classrooms and the development of simple language modules tailored to students’ needs. The methods used include initial observation, coordination with the school, provision of reading corners, development of learning modules, and assistance in the use of modules in the classroom. The results of the activity showed an increase in students’ interest in reading, increased use of free time for literacy activities, and ease for teachers in delivering language material. This program is expected to be the first step in forming a sustainable reading culture in the school environment. The sustainability of the program requires the support of teachers, schools, and student involvement in maintaining and utilizing the available literacy facilities.